2009 IEEE International Workshop on Advanced Methods for Uncertainty Estimation in Measurement 2009
DOI: 10.1109/amuem.2009.5207608
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty analysis for multi-stereo 3d shape estimation

Abstract: It is described the uncertainty analysis performed for the reconstruction of a 3D shape. Multiple stereo systems are employed to measure a 3D surface with superimposed colored markers. The described procedure comprises a detailed uncertainty analysis of all the measurement phases, and the evaluated uncertainties are employed to perform a compatibility analysis of points acquired by different stereo pairs. The compatible acquired markers are statistically merged in order to obtain a measurement of a 3D shape an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…We presented a general method for trinocular 3D reconstruction and outlier rejection. A further improvement could be the investigation of uncertainty of the SIFT features detector that may improve the outlier filtering by means of compatibility analysis (De Cecco et al 2009). An experimental setup has been built and tests have been performed in order to estimate system performances.…”
Section: Discussionmentioning
confidence: 99%
“…We presented a general method for trinocular 3D reconstruction and outlier rejection. A further improvement could be the investigation of uncertainty of the SIFT features detector that may improve the outlier filtering by means of compatibility analysis (De Cecco et al 2009). An experimental setup has been built and tests have been performed in order to estimate system performances.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al and Fooladgar et al demonstrated that quantization error is highly dependent on these factors by modelling the uncertainty volumes (see preceding section) rather than just the total magnitude in (1). Uncertainty volumes have also been used in other studies as a way to communicate the probabilistic nature of calculated 3-D point positions, for example De Cecco et al generated uncertainty ellipsoids to take into account the uncertainties from calibration and stereo matching [28].…”
Section: Geometric Constraints On Localization Errormentioning
confidence: 99%
“…This was chosen instead of a multi-stereo approach that can provide a better accuracy, if uncertainty is properly estimated as in [6,7]. Differently, multi-camera provides smoother points trajectories while multi-stereo reconstruction tends to generate marker "jumps" from one stereo pair to another, which ends up with also a jump in the corresponding 3D position.…”
Section: Image Processing For Shape Reconstructionmentioning
confidence: 99%